2011
DOI: 10.7589/0090-3558-47.4.880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella in Fecal Samples of Western Grey Kangaroos (Macropus Fuliginosus)

Abstract: This is the first extensive study of the prevalence of naturally acquired Salmonella infection in wild-caught kangaroos in Australia. Given the close association between kangaroos, livestock, and humans and the growing popularity of kangaroo meat, it is important to identify epidemiologic factors associated with infection in these marsupials in order to minimize the risk of Salmonella transmission. The overall prevalence of fecal Salmonella in 645 western grey kangaroos (Macropus fuliginosus) sampled across 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…However, it has been reported as a cause of clinical salmonellosis with positive blood cultures in children at the Children's Hospital, London, Ontario, Canada (Cellucci et al 2010), and has been implicated in human infection from feral pigeons. It also has been isolated from beef samples in Morocco and from faecal samples of kangaroos in Australia (Haag-Wackernagel & Moch 2004;Bouchrif et al 2009;Potter et al 2011). Isolation of a novel Salmonella serovar (S. Kiambu) from a dog indigenous to a developing country like Grenada is important to understand the possible role of domestic animals in the spread of novel pathogenic Salmonella serovar in the environment and zoonotic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported as a cause of clinical salmonellosis with positive blood cultures in children at the Children's Hospital, London, Ontario, Canada (Cellucci et al 2010), and has been implicated in human infection from feral pigeons. It also has been isolated from beef samples in Morocco and from faecal samples of kangaroos in Australia (Haag-Wackernagel & Moch 2004;Bouchrif et al 2009;Potter et al 2011). Isolation of a novel Salmonella serovar (S. Kiambu) from a dog indigenous to a developing country like Grenada is important to understand the possible role of domestic animals in the spread of novel pathogenic Salmonella serovar in the environment and zoonotic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rainfall was also associated with lower carriage of Salmonella in mongoose feces [ 29 ], and a negative correlation was found between rainfall the previous 30 days prior to sample collection and Salmonella excreted by quokkas ( Setonix brachyurus ), an Australian marsupial [ 69 ]. Dietary shifts associated with rainfall have been hypothesized to alter the intestinal microbiota and influence fecal shedding of Salmonella in free-ranging kangaroos [ 43 ]. It has also been suggested that rainfall might help disseminate Salmonella throughout the environment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct seasons were considered: rearing (May–July) and pre-denning/dispersal (August–October) as defined by Rosatte et al [ 38 ]. Sum of rainfall and mean temperature prior to 30 days of sample collection were used because this time period for rainfall was found to be significantly associated with Salmonella carriage in free-ranging wildlife in other studies [ 29 , 43 ]. Mean daily temperature and total rainfall per day were downloaded from Environment Canada from the nearest weather station with complete data (Fergus Ministry of the Environment (MOE), ON) from 2011 to 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Toads are therefore a potential vector for the spread of salmonellosis. In a recent study, in Australia, on kangaroos, prevalence of Salmonella was significantly associated with rainfall (Potter et al., 2011). Additionally, Haley et al.…”
Section: Discussionmentioning
confidence: 99%